Preferred language used by british and VietNamese hosts of television programmes - Nguyen, Tra Mi (2020)
Mi, N.T. (2012). Preferred language used by British and Vietnamese hosts of television programmes. A Bachelor’s Thesis submitted to Vietnam National University, University of Foreign Languages and International Studies. The development of television broadcasting has brought a variety of British and Vietnamese programmes to viewers. Using language, the hosts play the representative role and convey the message of the programmes. This paper shed light on characteristics of the languages used by British and Vietnamese TV programme hosts, as one of the attempts to help the audience apprehend the programme content. For the accomplishments of these purposes, the study carried out in the light of intercultural communication and is based on the authentic data collected. The findings of the study provide evidence that the languages used by British and Vietnamese hosts have certain similarities and differences. Each of the two languages pertains to its culture and reflects the essential values of the society.